PENGARUH PROMOSI SOSIAL MEDIA TERHADAP PEPUTUSAN BERKUNJUNG WISATAWAN DOMESTIK KE BALI ZOO (Jurnal Destinasi Pariwisata, 2025)
This study aims to analyze the influence of social media promotion on domestic tourists' decisions to visit Bali Zoo. With the growing reliance on digital platforms in the tourism industry, understanding the effectiveness of social media as a promotional tool becomes crucial for destination management. Bali Zoo, despite having a strong presence on Instagram with over 80,000 followers, faces relatively low engagement rates from its audience. This raises the need to explore and evaluate the effectiveness of its current social media strategies. The study employs observation and questionnaire distribution methods, targeting 100 domestic tourist respondents selected through purposive sampling techniques. The analysis is carried out using a simple linear regression model to measure the impact of social media promotion (independent variable) on tourists' visit decisions (dependent variable). Findings from this research reveal that enhanced social media promotion has a significant and positive influence on increasing the number of tourist visits. The study highlights the importance of well-targeted digital marketing strategies in not only attracting potential visitors but also in strengthening their engagement with tourism destinations. By leveraging visual content, interactive features, and strategic use of hashtags on platforms like Instagram, destinations like Bali Zoo can effectively reach a broader audience. Additionally, the findings emphasize the role of user-generated content (UGC) in building credibility and trust among prospective tourists. This research provides valuable insights for tourism stakeholders on optimizing social media platforms to enhance destination branding, improve audience engagement, and ultimately drive visitor numbers.
Keywords: Social Media Promotion; Tourists, Bali Zoo; Digital Marketing